Practical strategies for integrating strength and conditioning into early specialization sports - Moeskops, S.; Oliver, J. L.; Read, P. J.; Cronin, J. B.; Myer, G. D.; Lloyd, R. S. (Strength and Conditioning Journal, 2022)
Early sport specialization involves physically immature children participating in intensive year-round training and/or competition for a single sport. The lack of sport exposure and diversification during the developmental years may underlie the increased risk of overuse injuries, blunting of motor skill development, psychosocial issues, overtraining syndrome, burnout, and potential dropout from sport. With increasing number of youth choosing, or being encouraged, to specialize at an early age, we aim to provide evidence-based recommendations for the integration of strength and conditioning into the development programs of young athletes who participate in sports with a culture of early specialization. In addition to the principles of programming, strategies are provided relative to monitoring of growth, maturation, and training load to illustrate the potential complexities of attempting to optimize long-term athletic development in early specializing athletes.